Aromatase inhibitors in post-menopausal endometriosis - Devroey Paul; Velasco Juan-Garcia; Kyrou Dimitra; Grimbizis Grigoris; Zavos Apostolos; Fatemi Human M; Polyzos Nikolaos P; Tarlatzis Basil; Papanikolaou Evangelos G (BMC, 2011)
Abstract Postmenopausal endometriosis is a rare clinical condition. The diagnosis and treatment of an endometriotic lesion in postmenopausal women is complicated. First line treatment choice should be surgical, given that there is a potential risk of malignancy. Medical treatment may be considered as second line or as an alternate first line treatment whenever surgery is contradicted and aims to alter the hormonal pathway leading to endometriosis progress. Different hormonal regimens have been administered to these patients, with conflicting however results. Aromatase inhibitors (AIs) represent one of the most recently used drugs for postmenopausal endometriosis. Clinical data for the use of (AIs) in postmenopausal patients is scarce. Up to date only 5 case reports are available regarding the use of these agents in postmenopausal women. Although definite conclusions may be premature, AIs appear to considerably improve patients' symptoms and reduce endometriotic lesions size. Nonetheless the subsequent induced reduction in estrogen production, leads to certain short-term and long-term adverse effects. Despite the limited available data, AIs appear to represent a new promising method which may improve symptoms and treat these patients, either as first line treatment, when surgery is contraindicated or as a second line for recurrences following surgical treatment. However, careful monitoring of patients' risk profile and further research regarding long-term effects and side-effects of these agents is essential prior implementing them in everyday clinical practice.